UMP establishes Institute of Civilisation and Strategic Studies - Siti Nur Azwin, Zulkapri (2020)
KUALA LUMPUR, 4 December 2020 – Universiti Malaysia Pahang (UMP) has established the Institute of Civilisation and Strategic Studies (ITKAS) which will serve as a strategic research centre to support the development agenda and optimise the potential in various aspects, especially in Pahang.